Survey of Indian Currents: SOME HINDU CRITIQUES OF THE SECULAR STATE IN INDIA - Sharma, Arvind (Journal of Dharma, 2001)
I would like to develop the case against the secular state from a Hindu standpoint. The position or positions I will assume in the course of developing this case do not reflect my own thinking on the subject but rather the broad spectrum of views I have encountered when the case against the secular state is argued from a Hindu standpoint, In the course Of these discussions one could identify three broad approaches critical of the secular state in India. For the sake of convenience I shall label these as: The extremist Hindu critiques; The Hindu nationalist critique, and The liberal Hindu critique.